Ghana Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Follow-up Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Ghana Africa RISING follow-up evaluation survey was implemented in 2020. The survey data were collected from the same households that were interviewed as part of the Ghana baseline evaluation survey. Please refer to "A User Guide to Ghana Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey Data" data paper for details about survey coverage and design. The Ghana follow-up survey was implemented using structured questionnaires that were highly comparable with the questionnaires used in the Ghana baseline evaluation survey.